Development of Diabetes Education on Online-based Application: Telemondia - Atyanti Isworo; Yogi Ramadhani; Akhyarul Anam; Wahyu Ekowati; Ariesta Salwa Azalia (UM Purwokerto Press, 2021)
During the Covid 19 pandemic, a safe, efficient and effective educational method for diabetes patients is needed. Currently, an online-based education has developed, but this education is one-way, so the monitoring process is not getting enough attention. For this reason, it is necessary to develop online-based education in two directions so that there is interaction between patients, families and health workers. The purpose of this study is to develop a two-way online application-based education. The research method is research and development design. In the first phase, an online-based education development will be carried out with stages of design activities, validation and application acceptance testing. The results showed that an online application-based educational prototype named Telemondia had been composed and was validated by two diabetes education experts and two IT (Information Technology) experts. The following results from expert validation show the average aspect of ease of use of application is 90%; content clarity is 96.87%; aesthetic is 84.75%; instructional quality is 87.5; and feedback quality is 85.42% , with an average overall aspects of 87.87%. This shows that Telemondia is very feasible to use. Furthermore, in the acceptance test for 25 diabetic patients, the results of this acceptance test show ease of use of application is 92%; content clarity is 93%; aesthetic is 84%; instructional quality is 87; and feedback quality is 86%. The average overall aspect is 88.11%, which means that Telemondia can be accepted by patients. Further development will be made to add features that allow recording audio and video.